Temporal Variation of Reference Evapotranspiration in Lower River Kaduna Catchment Area, Nigeria - Auwal F. Abdussalam; Isa Zaharaddeen (Archives of Current Research International, 2017)
Lower River Kaduna catchment area is located in north part of Nigeria where climate variability is pronounce such as high rainfall which result to drought, ground water scarcity and high surface water to evaporation. As such it is importance to investigate the temporal variation evapotranspiration of this area. Because it determined the atmospheric water demand in the catchment. Meteorological data were collected from Nigeria Meteorological Agency which include mean temperature and solar radiation for the period of 21 years (1994-2014). Makkink method of estimating evapotranspiration was used. Trend analysis, normality test and coefficient of variance were carried out respectively. The result revealed that the evapotranspiration has mean value of 4.22 mm day-1, solar radiation has mean value of 21.48 MJ m−2 day−1and temperature has mean value of 32.07°C. Both variables show a moderate variability in the catchment. Evapotranspiration and solar radiation show a negative annual trend while the temperature reveals positive annual trend. April to October has decrease of solar radiation, temperature and evapotranspiration while the remaining month has an increase trend. Seasonal trend shows that MAM and JJA have a decrease while SON and DJF have an increase in solar radiation and evapotranspiration. Seasonal trend of temperature show that MAM, JJA and SON has a decrease while DJF has an increase.